2017
DOI: 10.1111/ijfs.13682
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the phenolic compounds and antioxidant capacity of five fruit (apple, orange, grape, pomelo and kiwi) juices during in vitro‐simulated gastrointestinal digestion

Abstract: Summary The in vitro digestive stability of phenolic compounds and the antioxidant capacity of five kinds of commonly consumed fruit juices in the daily diet, including apple juice (AJ), orange juice (OJ), grape juice (GJ), pomelo juice (PJ) and kiwifruit juice (KJ), were studied. Following in vitro digestion, the total phenolic (TP) content of fruit juices decreased to different extents by 35%, 25.3%, 23.5%, 22.2% and 7.8% for KJ, OJ, PJ, GJ and AJ, respectively. The individual phenolic content showed similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 58 publications
2
23
1
Order By: Relevance
“…Nevertheless, the use of 1‐MCP may reduce the production of aromatic substances (Balbontín, Gaete‐Eastman, Vergara, Herrera, & Moya‐Leon, 2007; Guo, Qiao, Zhang, Ren, & Li, 2018), although it can delay the ripening of fruit. Furthermore, consumer difference tests indicated that people can differentiate the 1‐MCP‐treated apples from the control group (Marin, Colonna, Kudo, Kupferman, & Mattheis, 2009; Quan et al., 2017). So the commercial application of 1‐MCP on fruit is restricted and unfeasible.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of 1‐MCP may reduce the production of aromatic substances (Balbontín, Gaete‐Eastman, Vergara, Herrera, & Moya‐Leon, 2007; Guo, Qiao, Zhang, Ren, & Li, 2018), although it can delay the ripening of fruit. Furthermore, consumer difference tests indicated that people can differentiate the 1‐MCP‐treated apples from the control group (Marin, Colonna, Kudo, Kupferman, & Mattheis, 2009; Quan et al., 2017). So the commercial application of 1‐MCP on fruit is restricted and unfeasible.…”
Section: Introductionmentioning
confidence: 99%
“…The content of TPC ranged from 374.7 to 791.4 mg EAG L −1 , vitamin C from 17.55 to 56.27 mg 100 g −1 , and antioxidant activity from 36.06% to 83.33% (Table ). The TPC content was in the range observed in orange juice (607.9 mg EAG L −1 , Table ), peach juice (400–1,620 mg EAG L −1 ; Saidani et al, ), apple juice (200–600 mg EAG L −1 , Persic, Mikulic‐Petkovsek, Slatnar, & Veberic, ), grape juice (500 mg EAG L −1 , Quan et al, ), and pomelo juice (500 mg EAG L −1 , Quan et al, ), but lower than those observed in pomegranate juice (1,385–9,476 mg EAG L −1 , Hmid, Elothmani, Hanine, Oukabli, & Mehinagic, ) and kiwi juice (1,000 mg EAG L −1 , Quan et al, ). The antioxidant activity was similar those reported in previous studies (Hmid et al, ; Saidani et al, ).…”
Section: Resultsmentioning
confidence: 80%
“…Quan et al . () studied the in vitro digestive stability of phenolic compounds and the antioxidant capacity of five kinds of commonly consumed fruit juices in the daily diet, and the results showed that following in vitro digestion, the total phenolic content and individual phenolic content of fruit juices decreased, while the antioxidant capacity of fruit juices during digestion measured by ABTS assay increased, illustrating that the health benefits of fruit juices after processing and contribute towards establishing suitable dietary recommendations. The antioxidant activity of digested dried lychee pulp is related to the change of monomer phenolic content.…”
Section: Discussionmentioning
confidence: 99%